2017
DOI: 10.11648/j.ijnrem.20170205.12
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Assessment of Heavy Metals in Surface Waters of the Middleton River in the Niger Delta, Nigeria

Abstract: This study was aimed at assessing the bioavailability of heavy metals in the surface water of the Middleton river which is a tributary of the river Nun located in the Niger Delta area of Nigeria. Samples were collected at points within and around oil and gas installations in the area while control points were chosen farther from identified pollution point sources. Three replicate samples were collected for each sampling and control location on a biannual basis for two months (March and August 2017) to reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Heavy metals distribution in the area was in the order; iron > zinc > chromium > lead > copper > nickel > cadmium. Similarly, the concentration of heavy metals in the study area is close to values previously reported in cassava mill effluents contaminated soil in a rural community in the Niger Delta, Nigeria by Izah et al, 20 In addition, values were within the range reported in sediments of the Nun River in the Niger Delta as reported by Aigberua et al, 54,55 Metal concentrations reflected high level of spreading across the various locations. The coefficient of variation (C.V) was very high for the individual heavy metals viz: zinc (73.96%), lead (84.45%), cadmium (38.06%), copper (94.12%), chromium (112.47%), nickel (71.35%) and iron (69.90).…”
Section: Resultssupporting
confidence: 89%
“…Heavy metals distribution in the area was in the order; iron > zinc > chromium > lead > copper > nickel > cadmium. Similarly, the concentration of heavy metals in the study area is close to values previously reported in cassava mill effluents contaminated soil in a rural community in the Niger Delta, Nigeria by Izah et al, 20 In addition, values were within the range reported in sediments of the Nun River in the Niger Delta as reported by Aigberua et al, 54,55 Metal concentrations reflected high level of spreading across the various locations. The coefficient of variation (C.V) was very high for the individual heavy metals viz: zinc (73.96%), lead (84.45%), cadmium (38.06%), copper (94.12%), chromium (112.47%), nickel (71.35%) and iron (69.90).…”
Section: Resultssupporting
confidence: 89%
“…The tidal nature of the river allows for the run-off of spilt crude into surrounding freshwater; this spilt crude sometimes emanate from the activities of bunkers within the environment, hence, it is not unusual to observe oil sheen on the water surface. As is typical of most communities living along the river shorelines in the Niger Delta region, other forms of indiscriminate and uncontrolled municipal discharges negatively impact on the overall quality of the aquatic environment (Aigberua et al, 2017). The predominant occupation of the inhabitants of Azuzuama community is majorly fishing and farming, the study area and sample locations are as shown in Figure 1.…”
Section: Study Areamentioning
confidence: 99%
“…Zinc: During the dry season, the distribution of zinc in sediment revealed that residual (31.7%) and water soluble (27.2%) were the most predominant fractions. This may have been partly responsible for the bioavailable concentrations of zinc in surface waters of the Middleton River (Aigberua et al, 2017). On the other hand, the wet season depicted mostly the immobile fractions as the residual (42.6%) and crystalline Fe-oxide (16.6%) were mostly predominant (Table 1).…”
Section: Heavy Metals Fractionation Patterns: Chromiummentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other forms of indiscriminate and uncontrolled municipal discharges negatively impact on the overall quality of the aquatic environment. 22…”
Section: Study Areamentioning
confidence: 99%